The German Reformation and Medieval Thought and Culture - Ocker, Christopher (History compass, 2012)
This essay asks the question, is it useful to approach the Reformation as a phase in a linear chronology, a movement away from the Middle Ages? On the example of Matthias Flacius Illyricus and the formation of Lutheran identity in the third quarter of the sixteenth century, I argue that Protestants had a vested interest in the continuity of their beliefs with medieval thought and culture. The familiar idea of a medieval-Reformation rupture is largely an invention of the nineteenth century. The research of recent decades, which I survey, has shown the limitations of this idea. I conclude with a proposal for seeing cultural change within multiple, overlapping chronologies.